2022
DOI: 10.3389/fmars.2022.875869
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management

Abstract: Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Along the North Sea coast of continental Europe and the UK, the harbour seal is an abundant predator and regarded as a key species in this ecosystem 3 , 14 . Previous studies have assessed the movement and habitat utilisation of harbour seals within the North Sea and adjacent coastal waters 13 , 15 , 53 , 54 . While there have been sightings of harbour seals in rivers and estuaries 19 , 20 , no studies have focused on how these seals utilise such brackish and fresh water environments adjacent to the North Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Along the North Sea coast of continental Europe and the UK, the harbour seal is an abundant predator and regarded as a key species in this ecosystem 3 , 14 . Previous studies have assessed the movement and habitat utilisation of harbour seals within the North Sea and adjacent coastal waters 13 , 15 , 53 , 54 . While there have been sightings of harbour seals in rivers and estuaries 19 , 20 , no studies have focused on how these seals utilise such brackish and fresh water environments adjacent to the North Sea.…”
Section: Discussionmentioning
confidence: 99%
“… (A) At sea distribution (a proxy for animal density) of the two seal species on the east coast of Scotland (Carter et al 2020) and the 30 km radius areas of low and high densities are shown on the two left maps. The locations of the low‐ and high‐density areas for harbour porpoise in the Inner Danish water are shown in the right‐hand map.…”
Section: Methodsmentioning
confidence: 99%
“…We also used satellite tracking data from 12 adult HS and 19 adult GS that were tagged on the east coast of Scotland between 2008 and 2013 (see Carter et al 2020 for details on tagging and data processing). The duration of deployment was 10-160 days (mean 85 days) for HS and 14-230 days (mean 85 days) for GS For each simulated or tagged individual.…”
Section: Estimating Individual Probabilities Of Exposure and Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…Following a post-weaning fast, during which they lose up to 25% of their body mass (Noren et al ., 2008), pups leave their natal site and move into an exploratory dispersal phase before settling, often a considerable distance from their place of birth (Carter et al ., 2020; Peschko et al ., 2020). Outside the breeding season, grey seals exhibit local redistributions and partial migration to foraging grounds – often several hundred kilometres offshore and are dispersed at much lower densities (Sayer et al ., 2021; Carter et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%